2014
DOI: 10.1002/cncr.29146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biochemical failure classification on clinical outcome: A secondary analysis ofRadiationTherapyOncologyGroup 9202 and 9413

Abstract: BACKGROUND Biochemical failure (BF) after radiation therapy is defined on the basis of a rising prostate-specific antigen (PSA) level (A1 failure) or any event that prompts the initiation of salvage androgen-deprivation therapy without PSA failure (A2). It was hypothesized that A2 failure may have a different prognosis. METHODS Data for 2799 eligible patients from Radiation Therapy Oncology Group (RTOG) 9202 and RTOG 9413 were analyzed. BF was defined according to the 1997 American Society for Therapeutic Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“….4 (95% CI 4.3-48.8) and 1.35 (95% CI 1.07-1.71) to 10.8 (95% CI 3.1-37.9). Similarly, for patients with RT as primary treatment, 8 out of 8[16,62,65,70,71,73,75,77], 5 out of 8[15 17,59,61,62,65,72] and 7 out of 9[15 17,58,59,61,62,64,71] studies showed a positive association between a higher Gleason score identified on prostate biopsies (bGS) and DM, PCSM and OM respectively with HRs ranging from 1.7 (95% CI 1.1-2.7) to 3.7 (95% CI 1.4-10.3), 2.11 (95% CI 1.03-4.34) to 14.8 (95% CI 2-110) and 1.8 (95% CI 1.3-2.4) to 17.9 (95% CI 9.6-33) respectively. Only a limited number of studies used the recently introduced ISUP grading in their MVA, allowing for a comparison between ISUP grade 2 and 3.…”
mentioning
confidence: 99%
“….4 (95% CI 4.3-48.8) and 1.35 (95% CI 1.07-1.71) to 10.8 (95% CI 3.1-37.9). Similarly, for patients with RT as primary treatment, 8 out of 8[16,62,65,70,71,73,75,77], 5 out of 8[15 17,59,61,62,65,72] and 7 out of 9[15 17,58,59,61,62,64,71] studies showed a positive association between a higher Gleason score identified on prostate biopsies (bGS) and DM, PCSM and OM respectively with HRs ranging from 1.7 (95% CI 1.1-2.7) to 3.7 (95% CI 1.4-10.3), 2.11 (95% CI 1.03-4.34) to 14.8 (95% CI 2-110) and 1.8 (95% CI 1.3-2.4) to 17.9 (95% CI 9.6-33) respectively. Only a limited number of studies used the recently introduced ISUP grading in their MVA, allowing for a comparison between ISUP grade 2 and 3.…”
mentioning
confidence: 99%
“…For DM and PCSM, 12 out of 14[7,8,22,23,26 28,38,39,41,43,52,53,56] and 10 out of 13[7,22,25,31,33,36,38 40,48 50,52] studies showed a positive association with HR ranging from 1.2 (95% CI 1-1.5) to 14.4 (95% CI 4.3-48.8) and 1.35 (95% CI 1.07-1.71) to 10.8 (95% CI 3.1-37.9). Similarly, for patients with RT as primary treatment, 8 out of 8[16,62,65,70,71,73,75,77], 5 out of 8 [15 17,59,61,62,65,72] and 7 out of 9 [15 17,58,59,61,62,64,71] studies showed a positive association between a higher Gleason score identified on prostate biopsies (bGS) and DM, PCSM and OM respectively with HRs ranging from 1.7 (95% CI 1.1-2.7) to 3.7 (95% CI 1.4-10.3), 2.11 (95% CI 1.03-4.34) to 14.8 (95% CI 2-110) and 1.8 (95% CI 1.3-2.4) to 17.9 (95% CI 9.6-33) respectively. Only a limited number of studies used the recently introduced ISUP grading in their MVA, allowing for a comparison between ISUP grade 2 and 3.…”
mentioning
confidence: 99%